ART NOUVEAU MASTERPIECE - RYABUSHINSKY MANSION (ResearchJet Journal of Analysis and Inventions, 2021)
The "modern" style is one of the most complex and even mysterious phenomena in the history of culture. Art Nouveau architectural monuments have been built in many parts of the world. One of these monuments is the Ryabushinsky Mansion in Moscow, also known as the A.M. Gorky, one of the best works of F.O. Shekhtel. It was built in 1900-1902. In the development of the history of world architecture architectural monuments of the Art Nouveau era occupy a special place. Examining the content of the article, the article is about one of the masterpieces of the Art Nouveau style - the Ryabushinsky mansion, built by F. Shekhtel.